RAMAN BAROMETRY OF DIAMOND FORMATION - Izraeli E.S.; Navon O.; Harris J.W. (My University, 1999)
Pressures and temperatures of the diamond source region are commonly estimated using chemical equilibria between coexisting mineral inclusions. Here we present another type of geobarometer, based on determination of the internal pressure in olivine inclusions and the stresses in the surrounding diamond. Using Raman spectroscopy, pressures of 0.13 to 0.65 GPa were measured inside olivine inclusions in three diamonds from the Udachnaya mine in Siberia. Stresses in the diamond surrounding the inclusions indicated similar pressures (0.11–0.41 GPa). Nitrogen concentration and aggregation state in two of the diamonds yielded mantle residence temperatures of ∼1200°C. Using this temperature and the bulk moduli and thermal expansion of olivine and diamond, we calculated source pressures of 4.4–5.2 GPa. We also derived a linear approximation for the general dependence of the source pressure (P0, GPa) on source temperature (T0, °C) and the measured internal pressure in the inclusion (Pi): P0=(3.259×10−4Pi+3.285×10−3)T0+0.9246Pi+0.319. Raman barometry may be applied to other inclusions in diamonds or other inclusion–host systems. If combined with IR determination of the mantle residence temperature of the diamond, it allows estimation of the pressure at the source based on a non-destructive examination of a single diamond containing a single inclusion.